Effects of Intravitreal Aflibercept on Galectin-1 and Vascular Endothelial Growth Factor-A Plasma Levels in Patients with Diabetic Retinopathy. (4th March 2018) - Waltl, Inga; Zehetner, Claus; Seifarth, Christof; Handle, Florian; Kieselbach, Gerhard F; Angermann, Reinhard; Kralinger, Martina T
ABSTRACT: Purpose : To analyze the interaction between aflibercept and galectin-1 and evaluate the plasma levels of galectin-1 and vascular endothelial growth factor (VEGF)-A after intravitreal injection of aflibercept in patients with diabetic retinopathy (DR). Methods : Interaction of galectin-1 with aflibercept was determined via immunoprecipitation. Seventeen patients with type 2 diabetes and diabetic macular edema (DME) were each treated with a single intravitreal injection of aflibercept (2.0 mg, 50 µL) monthly for three consecutive months. Plasma galectin-1 and VEGF-A levels were measured just before an injection was administered, 1 week after the first injection, and 2 months after the last injection. Nineteen age- and sex-matched healthy participants served as controls. Results : Irrespective of the tested galectin-1 concentration, 24% of added galectin-1 was precipitated by aflibercept. Baseline plasma concentrations of galectin-1 were 22.0 and 23.0 ng/mL in the control and aflibercept-treated groups, respectively. Systemic galectin-1 levels increased to 27.0 and 24.0 ng/mL at 7 days and 4 weeks, respectively, after treatment. At week 8, plasma galectin-1 levels significantly increased to 36.0 ng/mL. This level persisted for 20 weeks. Systemic VEGF-A levels significantly reduced to below the minimum detectable dose in 16 DME patients at 7 days after treatment. This level persisted for 4 weeks. Plasma VEGF-A levels were reduced at weeks 8 ( p = 0.099) and 20 ( p = 0.023). Decreased plasma VEGF-A levels were observed in all patients after treatment. Conclusion : We confirmed that physiological aflibercept levels precipitate galectin-1 in in vitro assays. Additionally, systemic upregulation of galectin-1 might be induced by intravitreal aflibercept, which may be relevant in the clinical outcomes of DR treatment.